An analytical study of annual bleeding rates in haemophilia patients receiving low dose factor prophylaxis and those receiving episodic factor doses - Pathradkar, Mrunal; Bafna, Varun; Paritekar, Anita (International Journal of Research in Medical Sciences, 2024)
Background: This study aimed to assess the impact of low dose factor prophylaxis on haemophilia patients with respect to annual bleeding rates and severity of bleeding events. Methods: This is an analytical study. All patients of HAEMOPHILIA A AND B who are registered with CPRH haemophilia treatment centre from January 2022 to December 2022 were included and were followed up every month from January 2022. The study population was divided into two groups: those receiving regular low dose factor prophylaxis and those receiving episodic factor treatment. Both the group participants were matched for severity of factor deficiency and age. The collected data was compared with respect to the annual bleeding rate as well as severity of bleeding episodes in the two defined groups. Results: There were 100 study patients, and 16 of them are receiving regular low dose factor prophylaxis. The average bleeding episodes were found to be more in patients receiving episodic factor doses (ABR in moderate haemophilia= 3.511+/-0.81, ABR in severe haemophilia=5.38+/-4, 53) as compared to those receiving prophylactic factor doses (ABR in moderate haemophilia = 0.16+/-0.32, ABR in severe haemophilia=0.3+/-0.29). The incidence of severe bleeds (those requiring hospitalisation) was higher in patients receiving episodic factor therapy (15) as compared to those receiving regular low dose factor prophylaxis (1). Conclusions: Haemophilia patients receiving episodic factor doses have higher Annual Bleeding Rate as compared to patients receiving regular low dose factor prophylaxis. Also, patients receiving prophylaxis face less severe forms of bleeding episodes as compared to other group of patients.